Temporal and site-specific variations in two bird assemblages: insights from anthropized landscapes in the Isthmus of Tehuantepec, Mexico (Avocetta, 2025)
The increasing prevalence of anthropized landscapes, often characterized by extensive agricultural practices and artificial infrastructure developments (e.g. wind farms), can lead to complex ecological scenarios where the functional roles of species within their communities are altered. This study aims to compare bird populations at two anthropized sites (Stipa and Sureste, Mexico) over a four-year period. Given their proximity (< 5 km) and the shared characteristic of being located within wind farm areas on agricultural ground, similarities in bird species composition were expected. During the study, 88,765 birds of 178 species were recorded. The results revealed comparable species richness at both sites, with 137 species observed at Stipa and 135 at Sureste. Differences in assemblage composition were significant between sites and seasons (fall vs. summer, fall vs. spring), but not between years. The dissimilarity between the two sites seems to be mainly influenced by the presence of waterbirds associated with an irrigation canal at Stipa and raptors associated with open areas at Sureste, likely a favourable habitat to maximize hunting success. The stable species assemblage structure observed over the study years suggests constant resource availability resulting from habitat homogenization driven by expanded sorghum cultivation displacing other crops. Conversely, variations in bird composition between seasons were influenced by migratory patterns, particularly among raptors, which became more abundant over the study years. This study supports the idea that artificial water supplies can favour the presence of bird species with an affinity for aquatic habitats in anthropized habitats, such as at Stipa. This highlights the importance of designing, regulating and well-managing artificial resources in anthropized landscapes, as these can contribute to habitat restoration, increase taxonomic diversity, and help achieve long-term conservation goals.